The impact of cafeteria diet feeding on physiology and anxiety-related behaviour in male and female Sprague-Dawley rats of different ages - Warneke, Wiebke; Klaus, Susanne; Fink, Heidrun; Langley-Evans, Simon C.; Voigt, Jörg-Peter (Elsevier, 2014)
There is emerging experimental evidence that hyper-energetic diets not only cause obesity but also impact on behaviour in rodents. A hyper-energetic comfort diet/cafeteria diet (CD) fed during early development programmes anxiety-related behaviour in adult age, but little is known how an obesogenic CD impacts on behaviour when fed at a later age.